Analysis of Teacher Competency and Work Ethic on Teacher Performance Through Work Motivation at State High School 19 Medan - Iqbal Syahputra; Husni Muharram Ritonga; Hernawaty Hernawaty (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Teacher performance is a strategic factor in determining the quality of the learning process and the achievement of educational goals in schools. Optimal teacher performance is influenced by various internal factors, including teacher competence, work ethic, and work motivation. This study aims to analyze the influence of teacher competence and work ethic on teacher performance, both directly and through work motivation as a mediating variable at SMA Negeri 19 Medan. This study used a quantitative approach with a survey method. The research population consisted of all civil servant teachers at SMA Negeri 19 Medan, totaling 89 people, who were also used as the sample (saturated sample). Data were collected through questionnaires and analyzed using the Partial Least Squares (PLS) method with the help of the SmartPLS application. The results showed that teacher competence and work ethic had a positive and significant effect on teacher performance. Teacher competence and work ethic also had a positive and significant effect on work motivation. Furthermore, work motivation has a positive and significant effect on teacher performance and is proven to act as a mediating variable in the relationship between teacher competence and work ethic on teacher performance. The coefficient of determination shows that teacher competence and work ethic can explain 42.3% of the variation in work motivation, while teacher competence, work ethic, and work motivation simultaneously explain 62.0% of the variation in teacher performance. The conclusion of this study confirms that improving teacher performance can be achieved by strengthening teacher competence and work ethic, supported by high work motivation. These findings are expected to serve as a basis for the school in formulating policies and strategies for continuous improvement of teacher quality at SMA Negeri 19 Medan.